ESG Score on Market Capitalization in Asean Countries - Fadilla; Choiriyah; Choirunnisak (The Islamic Education and Multiculturalism Foundation, 2024)
This research aims to determine the influence of E Score, S Score, and G Score on Market Capitalization values in ASEAN countries. The population of this study was 4591 companies. The sampling technique uses Simple Random Sampling, where we take a random sample of companies with a total of 49 companies. The data analysis technique uses multiple linear regression. The results of the analysis prove that there is an influence of E, S, and G Score together on market capitalization. However, partially only the E score has an influence on Market Capitalization, while the S and G Scores have no effect on market capitalization